1999
DOI: 10.1289/ehp.99107861
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behavior in Japanese quail as a test end point for endocrine disruption: effects of in ovo exposure to ethinylestradiol and diethylstilbestrol.

Abstract: Chemicals having a capacity to disturb the endocrine system have attracted considerable interest during recent years. There is a shortage of well-characterized in vivo tests with which to study such disturbances in different classes of vertebrates. In the present study, test end points related to reproduction in the Japanese quail were used to examine the estrogenic activity of chemicals. The synthetic estrogens ethinylestradiol (EE(2)) and diethylstilbestrol (DES), used as model compounds, were injected into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
33
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(45 citation statements)
references
References 52 publications
11
33
1
Order By: Relevance
“…Some of these compounds (e.g., bisphenol A or ethinylestradiol) are known to alter sexual behavior or reproduction in mammals as well as in birds (74). Halldin et al (75) described a significant reduction of sexual behavior in quail exposed to the environmental pollutant ethinylestradiol during embryonic development. It therefore seems of interest to investigate alterations of neural circuits that could influence these behavioral (and physiological) changes.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these compounds (e.g., bisphenol A or ethinylestradiol) are known to alter sexual behavior or reproduction in mammals as well as in birds (74). Halldin et al (75) described a significant reduction of sexual behavior in quail exposed to the environmental pollutant ethinylestradiol during embryonic development. It therefore seems of interest to investigate alterations of neural circuits that could influence these behavioral (and physiological) changes.…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, Gray et al (1982) observed a decrease in testicular weight. Embryonic exposure to xenoestrogens produced a reduction in the growth of the cloacal gland at sexual maturity in male Japanese quail (Adkins, 1979;Halldin et al, 1999;Halldin et al, 2003). This effect may be induced by activation of ERα since propyl pyrazol triol (PPT) treatment during quail embryo development significantly reduced the cloacal gland area in sexually mature males (Mattsson et al, 2008b).…”
Section: Effects On Histopathologymentioning
confidence: 99%
“…In many studies, male and female quail embryos have been treated with E 2 , E 2 esters and synthetic estrogen analogues to study their effect on development of reproductive tract, sexual maturation, behavior and egg-laying performance (Aste et al, 1991;Halldin et al, 1999;Berg et al, 2001). There is a limited number of studies concerning the effect of E 2 on Japanese quail egg production.…”
Section: Introductionmentioning
confidence: 99%
“…However, higher physiologic doses of E 2 stimulates the pituitary secretion of LH and FSH, which in turn stimulate gonadal function. However, addition of E 2 to pituitary cell culture inhibited or stimulated spontaneous secretion of FSH, depending on the species (Miller and Wu, 1981).In many studies, male and female quail embryos have been treated with E 2 , E 2 esters and synthetic estrogen analogues to study their effect on development of reproductive tract, sexual maturation, behavior and egg-laying performance (Aste et al, 1991;Halldin et al, 1999;Berg et al, 2001). There is a limited number of studies concerning the effect of E 2 on Japanese quail egg production.…”
mentioning
confidence: 99%